Economics of Timber Transportation by Skyline Crane - Kant, Hari; Sood, K. G. (Indian Forester, 1974)
Bulk of the forests in the hills are still exploited by the conventional methods comprising of felling by axes and saws and conversion in-situ by frame saws. This involves huge wastage from 50% to 63% The main reasons for not changing over to modern logging techniques are difficulty in handling logs and non-availability of heavy forest machinery indigenously at reasonable cost. If the logs are transported to a portable sawmill, a great proportion of the above wastage can be avoided. Manual transport of logs is time consuming and costly. Transportation by long distance Skyline Cranes is quicker and cheaper. This study bas been conducted on the economics of timber transportation by aindependent of the load. As such, it will be most economical if the machine is used for the full prescribed load capacity. The cost of long distance transportation by Wyssen Crane bas been worked out to be Rs. 26.44 per cu metre, of which about 50% is on account of the interest and depreciation of machinery. It is, therefore, inferred that if indigenously manufactured Skyline Cranes can be made available at reasonable price, the cost of extraction would be considerably reduced.